THE CONSTRUCTION OF DEBT PAYMENT ABILITY MODELS PREDICTIONS USING FINANCIAL INDICATORS BASED ON HISTORICAL COST ACCOUNTING AND GENERAL PRICE LEVEL ADJUSTED ACCOUNTING - Elizabeth Manurung (Indonesian Management and Accounting Research, 2009)
The purpose of this research is to measure the effect of economic crisis in Indonesia in the period of 1997 2001 and the effect of inflation on the financial indicators of the textile industries in West Java. Research method used descriptive analytic method, and the data used are collected by using a survey method. Using discriminant analysis and logistic regression the research find out that there are 8 models that can be used to predict the firm ability to pay their debt. The logistic regression using inflation accounting data turns out to be more accurate than the discriminant analysis. The logistic model using inflation data can predict correctly 95,4% of the actual data. The fact indicates that the high inflation rate during the crisis affect the financial condition which resulted the financial information about firms ability to pay their debt.Keywords: Financial indicators, Accounting inflation, Historical cost, debt payment ability.